Regulation of Syrm and Nodd3 in Rhizobium Meliloti - Swanson, J. A. (1993)
The early steps of symbiotic nodule formation by Rhizobium on plants require coordinate expression of several nod gene operons, which is accomplished by the activating protein NodD. Three different NodD proteins are encoded by Sym plasmid genes in Rhizobium meliloti, the alfalfa symbiont. NodD1 and NodD2 activate nod operons when Rhizobium is exposed to host plant inducers. The third, NodD3, is an inducer-independent activator of nod operons. We previously observed that nodD3 carried on a multicopy plasmid required another closely linked gene, syrM, for constitutive nod operon expression. Here, we show that syrM activates expression of the nodD3 gene, and that nodD3 activates expression of syrM. The two genes constitute a self-amplifying positive regulatory circuit in both cultured Rhizobium and cells within the symbiotic nodule. We find little effect of plant inducers on the circuit or on expression of nodD3 carried on pSyma. This regulatory circuit may be important for regulation of nod genes within the developing nodule.